Enriquecimento ambiental sobre o desempenho e comportamento de frangos de corte - Zago, Cláudia Helena Ferreira (2015)
The production of broilers focuses on system integration, where there is an exchange of information and diffusion of new technologies, between business and farmers with greater ease. In Brazil, the poultry industry is in good health status, unlike other regions of the world. This condition provide the country achievement and maintenance of external consumer markets. The agility in communication and information exchange prepares each day more the consumer market, that becomes more demanding. The main demand still is the product price, but a growing consumer market is looking for food with higher added value. In this context we can highlight the demand for screened products, with characteristics of environmental respect, social respect, animal welfare manners and production systems for energy saving. The broilers happens production is confined and controlled environments. Respect the environmental control in each phase is one of the points to ensure animal welfare, by providing conditions where the animal can respond with good performance, what it is genetically selected. Regarding the confinement of animals are being studied some alternatives to reduce stressful situations almost nil, because the equipment offer food and water easy. The use of perches in trading systems offers something that naturally the birds can do in their habitat: perch, and provide opportunity for greater movement. The lack of movement can hinder the development of locomotor system, causing deviations of the legs with limited mobility, lower feed intake and subsequent death of the birds. The following losses in the industry with footpad injuries, legs and carcasses. In this context the objective of this study is to contribute to the knowledge welfare and address the use of environmental enrichment on a commercial scale.